2012
DOI: 10.1111/j.1398-9995.2012.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological effects and tolerability of a new fast updosed immunologically enhanced subcutaneous immunotherapy formulation with optimized allergen/adjuvant ratio

Abstract: Fast updosed immunologically enhanced SCIT with an optimized allergen/adjuvant ratio induced significant immunological effects and had an acceptable safety profile. Clinical efficacy will be investigated in future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The incidence of systemic adverse reactions was 22.5% for group 1 and 35.1% for group 2 in Jung K. (31), and 21% or 33% of patients of group 1 and 2 respectively according to Pfaar O. (32).…”
Section: Discussionmentioning
confidence: 89%
“…The incidence of systemic adverse reactions was 22.5% for group 1 and 35.1% for group 2 in Jung K. (31), and 21% or 33% of patients of group 1 and 2 respectively according to Pfaar O. (32).…”
Section: Discussionmentioning
confidence: 89%
“…Biotechnology strongly contributed to the improvement of allergy vaccines by chemical modification of natural allergens and even more by genetic engineering of recombinant allergens starting from the natural sequences, the generation of hypoallergenic variants including isoforms and folding variants , and the de novo engineering of vaccines combining B‐ or T‐cell epitopes . Some of these experimental vaccines have been successfully tested in clinical trials and demonstrated to have an increased safety profile and reduced side‐effects compared with allergen extracts.…”
Section: Development Of Novel Vaccinesmentioning
confidence: 99%
“…ILIT has also been combined with modular antigen‐translocating vaccines which directly target the MHC class II antigen presentation pathway and showed excellent results in a phase I/IIa clinical study after only three injections of low amounts of vaccine . There is of course an increasing number of clinical trial reports involving many kinds of different biotechnologically engineered allergen vaccines which, in combination with different routes of application, indicate a great therapeutic and economic potential for the future treatment and prevention of allergic and asthmatic diseases .…”
Section: Novel Routes Of Application: Scit Slit Ilit and Clinical mentioning
confidence: 99%
“…In a recent randomized, controlled, parallel-group trial from the authors' group, patients with grass pollen induced rhino conjunctivitis with/without asthma were treated with an optimized ratio of a grass pollen extract and adjuvant AH-SCIT formulation (AVANZ, ALK, Denmark) [58]. The trial included uptitration with five injections (300, 600, 3000, 6000 and 15,000 SQ+) injected in either weekly intervals (group 1) or intervals of 3-4 days (group 2) followed by two maintenance injections (15,000 SQ+) -approximately 10 weeks of treatment.…”
Section: Aluminum Hydroxidementioning
confidence: 99%